2014
DOI: 10.2503/jjshs1.mi-001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Root-zone Heating on Root Growth and Activity, Nutrient Uptake, and Fruit Yield of Tomato at Low Air Temperatures

Abstract: Low-cost heating is needed to reduce chilling injuries, heating costs, and CO 2 emission during greenhouse tomato production. To acquire information about the physiological and morphological effects of root-zone heating, an economical option at low air temperatures, we grew tomato plants on a nutrient film technique hydroponic system in a heated nutrient solution. We investigated the effects of short-term root-zone heating after transplanting and long-term heating until harvest. We measured short-term plant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 26 publications
(42 reference statements)
4
34
1
Order By: Relevance
“…Some similar studies have been reported (Kawasaki et al, 2013;Klock et al, 1997;Sasaki and Itagi, 1989). Around 20°C of root-zone heating increased leaf area, plant height, and relative growth rate (RGR) at low air temperature (16.2°C of daily mean temperature) (Kawasaki et al, 2014). In cucumber and tomato plants, the photosynthesis rate, stomatal conductance and shoot RGR increased with root-zone heating from 13°C to 19°C at an air temperature of 20/12°C (Wang et al, 2016).…”
Section: Local Temperature Control Of Rootssupporting
confidence: 58%
See 2 more Smart Citations
“…Some similar studies have been reported (Kawasaki et al, 2013;Klock et al, 1997;Sasaki and Itagi, 1989). Around 20°C of root-zone heating increased leaf area, plant height, and relative growth rate (RGR) at low air temperature (16.2°C of daily mean temperature) (Kawasaki et al, 2014). In cucumber and tomato plants, the photosynthesis rate, stomatal conductance and shoot RGR increased with root-zone heating from 13°C to 19°C at an air temperature of 20/12°C (Wang et al, 2016).…”
Section: Local Temperature Control Of Rootssupporting
confidence: 58%
“…In tomato plants, root-zone cooling from 33°C to 17°C at an air temperature of 35/22°C (day/night) increased water and nitrogen absorption, as well as enhancing xylem exudation (Nakano, 2007). Similar effects were also reported by root-zone heating and indicated that mineral nutrient transport to shoots was accelerated by xylem vessels (Kawasaki et al, 2014). These effects resulted in an increased mineral nutrient content in shoots (Gent and Ma, 2000;Klock et al, 1997;Nkansah and Ito, 1995b;Papadopoulos and Tiessen, 1987).…”
Section: Local Temperature Control Of Rootsmentioning
confidence: 71%
See 1 more Smart Citation
“…The selected functional unit is 1 kg of tomato. For the analysis we suggested an increase of 20% of productivity for the new scenarios (A,B,C and D) according to the benefits of root zone temperature control found in the literature [3,4]. Climate Change and CED indicators obtained from these scenarios were also compared with the referent scenario from the EUPHOROS project [21] which does not use any heating or cooling system.…”
Section: Titlementioning
confidence: 99%
“…Root zone heating can decrease fuel consumption [1] while obtaining the same productivity achieved with traditional heating systems [1,2]. The use of root zone climate systems stimulates productivity [3,4] if other key parameters as humidity, solar radiation, nutrients or environmental temperature are controlled properly.…”
Section: Introductionmentioning
confidence: 99%